Potential of Small and Medium Enterprises Growth: Role of Internal and External Factors of Commercial Banks’ Credit Accessibility - Abolaji Oladimeji, Odumesi; Timilehin Olasoji, Olubiyi; Kowo Solomon, Akpoviroro (INTI International University, 2024)
The common factors determining Commercial banks’ lending to SMEs are internal and external factors. This study assessed the combined effect of these two factors that determine the commercial banks’ credit accessibility and SMEs’ growth in Nigeria. Data from 1990 to 2023 were used to evaluate the hypothesis. The outcome demonstrates that internal factors of commercial bank factors on credit accessibility to SMEs was 0.039110 and statistically significant at the 5% level (p-value = 0.0254). The outcome suggests that internal factors of commercial bank determinants on the availability of credit to SMEs play a significant impact in the expansion of SMEs in Nigeria. At the 5 percent level, the external influence of commercial banks on SMEs' access to credit was -0.014003 and statistically insignificant (p-value = 0.2757). The results will substantially aid in designing and implementing monetary policy with regard to the cash reserve requirement. It also conveys to SMEs the significance of cash reserve requirement in improving loan accessibility in Nigeria. As a result, the paper recommends that monetary policy be continually improved to favour SMEs because doing so will facilitate their expansion.